2017
DOI: 10.15835/nbha45110728
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Accumulation and Antioxidant Potential of Dracocephalum moldavica L. Cell Suspension Culture

Abstract: Dracocephalum moldavica L. (Lamiaceae) is known for its medicinal properties; however greater yields can potentially be achieved by in vitro cultivation. A cell suspension culture of D. moldavica L. (Lamiaceae) derived from root-derived callus was established in liquid MS medium supplemented with 2,4-D 0.5 mg/l and BAP 0.2 mg/l. The biomass and rosmarinic acid (RA) content were analyzed during the 15-day growth cycle of the culture. The highest fresh and dry weight (14.29 g/flask and 1.14 g/flask, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…TFC was in the range from 23.9 ± 1.2 (in aqueous extract) to 79.3 ± 2.5 mg QE g ‐1 (in EtOAc extract). In the literature, the antioxidant activity and TPC of a 70% aqueous MeOH extract of D. moldavica was evaluated by (Weremczuk‐jeżyna et al., 2017 ). The TPC of the aerial parts of D. moldavica was 110.1 mg GAE g ‐1 , which was higher than observed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…TFC was in the range from 23.9 ± 1.2 (in aqueous extract) to 79.3 ± 2.5 mg QE g ‐1 (in EtOAc extract). In the literature, the antioxidant activity and TPC of a 70% aqueous MeOH extract of D. moldavica was evaluated by (Weremczuk‐jeżyna et al., 2017 ). The TPC of the aerial parts of D. moldavica was 110.1 mg GAE g ‐1 , which was higher than observed in our study.…”
Section: Resultsmentioning
confidence: 99%
“…High content of RA (27.2mg/g) was also present in 70% methanol extracts of cell suspension of D. moldavica herb, and this species was estimated as a good candidate for in vitro production of this compound. [ 27 ] The highest level of RA content was also established for the herbal infusion of D. moldavica among the other species of Nepetoideae subfamily by HPLC. [ 8 ] High content of this compound was also revealed in the aerial parts of some Salvia species.…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that high content of phenolic compounds as well as aromatic components in essential oils is well correlated with the antioxidant activity of plant materials of Lamiaceae representatives. [ 4 5 , 9 27 , 29 30 ] Therefore, according to the foregoing, investigated herbs have a potent antioxidant property due to high content of RA, and the presence of other spots of polyphenols in HPTLC chromatograms.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the Lamiaceae species have been used for studying the production of phenolic compounds in various in vitro systems, such as cell suspension (Weremczuk-Jeżyna et al 2017), callus and shoot culture (Karakas and Turker 2016) or hairy roots (Grzegorczyk-Karolak et al 2018). Usually, the yields were higher than in the shoot culture of M. laevis in our study.…”
Section: Discussionmentioning
confidence: 65%